Effect of Different Organic Manure Rates on Yield and Post Harvest Storage of Okra (Abelmoschus esculentus) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The experiment was conducted at the Research Farm of the Department of Crop Science and Horticulture, Nnamdi Azikiwe University, Awka, Nigeria to study the effect of different organic manure rates on yield and okra. Different manure sources from poultry and pig and the rates were: 0 ton/ha, 5 tons/ha, 10 tons/ha, 15 tons/ha, and 20 tons/ha. The 2 x 5 factorial experiment was laid out in a Completely Randomized Design (CRD) and replicated three (3) times. Data were collected on growth and yield. For yield parameters, pig manure at15 t/ha rate gave the highest yield however, the interaction effects showed that 15t/ha poultry manure x yield produced the highest number and weight yield of pods, while 15 t/ha pig manure out performed in the length and width of okra pods. Hence, poultry manure at 15t/ha and 20t/ha pig manure were recommended. Considering the effect of postharvest storage materials on the physiological deterioration rates of okra pods, newspaper, and dried plantain leaves maintained better postharvest storage quality of okro than other storage materials.
Keywords: Deterioration; Growth and yield parameters; Okra pods; Post- harvest; Poultry and pig manure